Strategic Choiceand Performance: An Overview Of Institutions Of Higher Learning - Awino, Zachary Bolo; Ayuya, Angeline Mukokho; Machuki, Vincent N.; Wainaina, Gituro (Archives of Business Research, 2018)
Organizational performance is critical for both empirical and conceptual research in strategy. Strategic choice serves as a major connection between the organization and the environment in which it operates and involves decisions on the mix of business portfolio. Scholars attribute the strategic choices which determine organizational performance to the type of strategies they choose, yet there is no agreement on the extent to which these strategic choices influence performance. This paper sought to contribute to knowledge by assessing the extent to which strategic choice influences organizational performance. The objective of this paper was to establish the influence of strategic choice on organizational performance. The research used a cross-sectional survey. This study used a sample of fifty-two (52) private and public accredited universities. Both primary and secondary data was collected using semi-structured questionnaires. An analysis was done using correlation and regression analysis to test the hypotheses. The objective confirmed significant results on non-financial performance. The findings of this research are consistent with most of the previous studies. This study therefore extends the knowledge frontiers in strategic management through the finding that strategic choice influences organizational performance. The findings provide a diversity of implications on theory, policy, and practice. Policymakers will utilize the findings from this study as a guide in the policy formulation and implementation of strategic choices aimed at the success of the institutions of higher learning.